Environmental governance in oil-producing developing countries : findings from a survey of 32 countries (World Bank, 2010)
The Petroleum Governance Initiative (PGI) encompasses three general themes, or pillars, that address issues issues of transparency and economic responsibility, environmental sustainability and responsible community development. Of particular interest here is the second pillar, environmental sustainability; the PGI is currently involved in four main activities surrounding this theme: 1) assessing environmental governance and management in oil-producing countries-the topic of this paper; 2) conducting a strategic environmental assessment of oil and gas activity in Mauritania; 3) conducting workshops and preparing a toolkit on decommissioning and abandonment; and 4) providing in-country assistance on environmental management to a limited number of countries. This paper presents the results of a survey undertaken by the PGI to measure the environmental governance of oil-producing nations against a benchmark standard representing a compendium of good management practices for minimizing impacts of oil and gas development. The objective is to identify areas where the World Bank can provide assistance to improve environmental governance and management systems, particularly in those developing countries whose oil and gas industry is rapidly emerging as a major component of gross domestic product. Detecting governance gaps-and, more importantly, facilitating the rapid implementation of corrective measures-is an important challenge for the World Bank in its efforts to preserve natural habitats and the culture of indigenous peoples.